2017
DOI: 10.1177/0284185117702181
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of high b-value diffusion-weighted MRI for prostate cancer detection: a meta-analysis

Abstract: Background: The diagnostic accuracy of diffusion-weighted imaging (DWI) to detect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…Our pooled results match those of meta-analyses investigating T 2 WI and DWI by Wu et al and Tan et al; this is likely due to the large overlap of included studies [ 28 , 29 ]. Compared with Godley et al and Jie et al who analyzed the use of DWI alone, we observed a higher sensitivity but lower specificity [ 5 , 30 ]. However, when we compare the results for just peripheral zone tumors, our pooled results are similar.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Our pooled results match those of meta-analyses investigating T 2 WI and DWI by Wu et al and Tan et al; this is likely due to the large overlap of included studies [ 28 , 29 ]. Compared with Godley et al and Jie et al who analyzed the use of DWI alone, we observed a higher sensitivity but lower specificity [ 5 , 30 ]. However, when we compare the results for just peripheral zone tumors, our pooled results are similar.…”
Section: Discussioncontrasting
confidence: 79%
“…Compared with Godley et al and Jie et al who analyzed the use of DWI alone, we observed a higher sensitivity but lower specificity [5, 30]. However, when we compare the results for just peripheral zone tumors, our pooled results are similar.…”
Section: Discussionsupporting
confidence: 55%
“…43,44 Despite some conflicting reports, the general consensus is that higher b-values can provide better conspicuity for tumor detection, provided that an adequate SNR (eg, 5-10) can be maintained. 45,46 This has led to recent adoption of high b-value (1400-2000 s/mm 2 ) DWI in Prostate Imaging Reporting and Data System (PI-RADS) Version 2. 47 Achieving an adequate SNR at high b-values can be challenging.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The potential value of high b-values for cancer detection has also been investigated in several other cancers 43,44 . Despite some conflicting reports, the general consensus is that higher b-values can provide better conspicuity for tumor detection, provided that an adequate SNR (e.g., 5–10) can be maintained 45,46 . This has led to recent adoption of high b-value (1400–2000 s/mm 2 ) DWI in Prostate Imaging Reporting and Data System (PI-RADS) Version 2 47 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Ahmed et al[1] found that the sensitivity of mpMRI for the detection of clinically significant disease was 93% (95%CI: 88%-96%), which was significantly superior to the sensitivity of TRUS biopsy (48%; 95%CI: 42%-55%). One meta-analysis showed that the pooled sensitivity and specificity of mpMRI for prostate cancer detection are 74% and 88%, respectively[16]. Assessment of lymph node involvement can be performed by both CT and mpMRI, but both have a very low sensitivity[17].…”
Section: Discussionmentioning
confidence: 99%